Potensi dan Pengembangan Manfaat Bambu dalam Industri Kreatif dan Pengendalian Produksi - Latif, Adi Sofyana; Ekarisma, Deny; Saga, Baharudin; Septanta, Rananda (Jurnal PKM Manajemen Bisnis, 2025)
Bamboo is a renewable natural resource with significant potential in the creative industry due to its versatility, sustainability, and economic value. However, its utilization remains limited, particularly among young communities. This community service activity aimed to explore and develop the potential benefits of bamboo in the creative industry and production control. The activity was conducted at Domyadhu Foundation, Pamulang, South Tangerang, involving 30 students from the Dompet Yatim dan Dhuafa boarding school. The program was facilitated by 10 lecturers from Pamulang University. The implementation consisted of three main stages: preparation, execution, and reporting. The method included material presentation, group discussions, and hands-on practice focused on bamboo processing, product innovation, and small-scale production management. The activity successfully increased participants' knowledge and skills in utilizing bamboo for creative purposes, such as crafting simple household and decorative items. Moreover, participants gained awareness of bamboo’s environmental and economic value. The program fostered creativity, entrepreneurial spirit, and a practical understanding of sustainable production among the students. This community service initiative highlights the importance of empowering youth with skills that align with local resources and sustainable development goals.